Comparison of Bureaucratic Neutrality in the 2019 and 2024 Elections From The Perspective of Online Mass Media in Achieving SDG 16 (Peace, Justice, and Strong Institutions) - Indiahono Dwiyanto; Rizky Pratama Bayu; Tobirin Tobirin; Rahmawati Titi; Azriah Thahrina (E3S Web of Conferences)
Bureaucratic neutrality is a value born from the same concern and respect in the public sphere in realising Peace, Justice, and Strong Institutions to achieve the Sustainable Development Goals (SDGs). The purpose of this article is to examine the issue of bureaucratic neutrality in local online mass media. The target of this research is the independent online voice, a reputable online mass media outlet in Central Java. The online independent vote was chosen because it has a national scope, provides the latest news related to socio-political discussions, narrates the government's steps and plans in preparing for the election, and visualises the policies the government prepared before the election. This study uses a content analysis approach. The study results show that in the 6 months before the 2024 election, Suara Merdeka Online reported 26 news. Meanwhile, in the 2019 elections, the online independent vote reported 40 news stories. In 2024, there is an average frequency of recurring main issues, namely neutrality, neutrality, and democracy posts, as well as guard bureaucratic neutrality. Meanwhile, in 2019, the dominance of content is a commitment to neutrality, securing elections, the threat of hoaxes and cyber, and the potential for election vulnerability.